Effects of pyrethroid insecticides on subjects engaged in packaging pyrethroids. Issue 8 (August 1988) - He, F; Sun, J; Han, K; Wu, Y; Yao, P; Wang, S; Liu, L
Abstract : A health survey was conducted on 199 workers engaged in dividing and packaging pyrethroids. The subjects were exposed to fenvalerate at 0.012-0.055 mg/m3 and deltamethrin at 0.005-0.012 mg/m3 in the air with simultaneous skin contact for 0.5-4.5 months. Burning sensations and tightness or numbness on the face appeared in two thirds of the subjects and one third had sniffs and sneezes. Abnormal facial sensations, dizziness, fatigue, and miliary red papules on the skin were more evident in summer than in winter. Neither abnormalities in other organs or systems nor symptoms or signs of acute pyrethroid poisoning were found by interviews, examinations, and laboratory tests. There was no significant difference in plasma levels of NA, cAMP, and cGMP between the examined subjects and the control group. The urine concentration of fenvalerate in the study group ranged from 1.02 to 18.6 micrograms/l; deltamethrin in the urine was present in trace amounts.